Harmony of Religious and Secular Values in The Spiritual and Moral Education of Youth - Dilorom Yuldasheva (Indonesian Journal Publisher, 2025)
This article explores the significance of harmonizing religious and secular values in the spiritual and moral upbringing of youth. In the context of globalization and rapid socio-cultural change, the moral stability of young people is increasingly vital. The article emphasizes that a balanced integration of religious teachings—particularly those rooted in Islam—with universal human values such as respect, tolerance, and civic responsibility can provide a strong foundation for ethical behavior. It also discusses how this synergy can help protect youth from harmful ideologies, including extremism and moral degradation. The study underscores the role of family, educational institutions, and society in fostering a value-based worldview that nurtures spiritually rich and socially responsible individuals